Security, It’s Concept and Implications in Quran | الأمن مفهومه ودلالاته في ضوء القرآن الكريم - Ahmaddin Ahmad Tohar (Al-Zahra : Journal for Islamic and Arabic Studies, 2016)
Feeling safe, secure and comfortable is a personal innate needs and human rights. It willgenerate good atmosphere and conclusive condition of worship, working environmentand competition for personal or others. The filling secure in Al Qur’an covers all sides ofthe human life world and the hereafter, as individuals and as a social being. Ayat-Ayat(Nash) Al Quran encourage people to create safety and comfortable atmosphere, indeed,if there is no guarantee it will have implications on community balancing, humangrowth and social welfare.